Answer:
The value is m = 3.
Step-by-step explanation:
Multiplication of terms with same base and different exponents:
When two terms with the same base and different exponents are multiplied, we keep the base and add the exponents.
In this question:
We have the following expression:
[tex](\frac{3}{8})^{2m} \times (\frac{3}{8})^6 \times (\frac{3}{8}) = (\frac{3}{8})^13[/tex]
Applying the property:
[tex](\frac{3}{8})^{2m+6+1} = (\frac{3}{8})^13[/tex]
[tex](\frac{3}{8})^{2m+7} = (\frac{3}{8})^13[/tex]
Since the bases are equal, we can equalize the exponents:
[tex]2m + 7 = 13[/tex]
[tex]2m = 6[/tex]
[tex]m = \frac{6}{2} = 3[/tex]
The value is m = 3.